2019
DOI: 10.1186/s12885-019-5865-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of segmental prosthesis reconstruction for diaphyseal bone tumors: a multi-center retrospective study

Abstract: Background The optimal reconstructive method after diaphyseal malignant bone tumor resection remains controversial. This multicenter clinical study was designed to investigate the clinical value and complications of segmental prosthesis in the repair of diaphyseal defects. Methods We present 49 patients from three clinical centers treated with wide resection for primary or metastatic bone tumors involving the diaphysis of the femur, tibia, humerus, or ulna, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
4
19
1
Order By: Relevance
“…However, Dijkstra et al found that IMN and plate fixation yielded similar results [ 15 ]. In the present study, the incidence of postoperative complications in the IMN group was 18.8% (3/16) and 21.2% (7/33) in the PF group, which were in the range of reported incidence rates in previous studies [ 8 , 9 , 13 15 , 19 , 20 , 28 , 34 36 ] (Table 4 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, Dijkstra et al found that IMN and plate fixation yielded similar results [ 15 ]. In the present study, the incidence of postoperative complications in the IMN group was 18.8% (3/16) and 21.2% (7/33) in the PF group, which were in the range of reported incidence rates in previous studies [ 8 , 9 , 13 15 , 19 , 20 , 28 , 34 36 ] (Table 4 ).…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, when possible, more radical treatment is needed for some patients with solitary bone lesions and a longer predicted life expectancy. Encouraging results regarding the application of intercalary prostheses have been obtained from studies on intercalary prostheses, leading to the expansion of surgical indications and controversy regarding the treatment of choice [ 13 , 19 , 20 ]. Additionally, mechanical studies conducted in vitro have indicated that prostheses provide a stronger construct than IMN does in a model of humeral segmental defects [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 ) are an alternative for intercalary reconstructions [ 4 ]. They allow immediate stability, rapid rehabilitation, and early weight bearing [ 24 , 104 ]. Common complications are infections, mechanical loosening, and mechanical wear [ 24 ].…”
Section: Reconstruction Using Non-biological Materialsmentioning
confidence: 99%
“…The main advantages of these grafts are their relative abundance, which allows reconstruction even after massive bone defect, and the absence of morbidity of the donor site [ 21 ]. The disadvantages, on the other hand, are immunological rejection and the risk of transmissive diseases, such as HIV and Hepatitis C [ 22 24 ]. However, these latter are reduced by modern screening methods [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation